VD_FINDINFO Décision / 2015 / 599 vom 26. Juni 2015 - VD Tribunal cantonal (2015)
NON-LIEU, DIFFAMATION, CALOMNIE, PRESCRIPTION, DÉLIT CONTINU, DÉNONCIATION CALOMNIEUSE | 14 CP, 173 CP, 174 CP, 303 CP, 310 CPP (CH)